Mapping violence in the Chilean countryside: San Bernardo, Buin, Isla de Maipo and Paine – 1973 - Nazario de Wergenes, Tiago; Cortes Darrigrande, Maria Macarena (Revista Historia y Patrimonio, 2024)
A significant number of studies on landscapes of memory focus on traumatic events perpetrated by the State or other political and armed forces against specific populations. This article aims to analyze these events, understand their development and examine how they leave their marks on the territory. Cartography emerges as a key tool in this analysis, prompting the question: how can these processes be mapped? One possible approach is to establish a “field,” which encompasses and delimits the territory, while selecting significant elements to be mapped and linked, providing a basis for case analysis. This study investigates a territory spanning four communes located in the southern sector of the Metropolitan Region of Santiago de Chile, marked by repressive episodes during the early months following the 1973 coup d’état. The mapping process involved identifying and selecting two types of elements/forces: “places” and “displacements,” which were analyzed and interrelated. The integration of these elements made it possible to visualize key aspects of the dynamics of repression, such as the scale of violent episodes, hierarchies among strategic locations, and patterns suggesting the existence of a plan for carrying out major repressive operations.